Biogeochemistry and timing of methane-derived carbonate formation at Leirdjupet fault complex, SW Barents sea - Argentino, Claudio; Lee, Amicia; Fallati, Luca; Sahy, Diana; Birgel, Daniel; Peckmann, Jörn; Bünz, Stefan; Panieri, Giuliana (Frontiers in Earth Science, 2022)
The origin of modern seafloor methane emissions in the Barents Sea is tightly connected to the glacio-tectonic and oceanographic transformations following the last ice age. Those regional events induced geological structure re-activation and destabilization of gas hydrate reservoirs over large areas of the European continental margins, sustaining widespread fluid plumbing systems. Despite the increasing number of new active seep discoveries, their accurate geochronology and paleo-dynamic is still poorly resolved, thus hindering precise identification of triggering factors and mechanisms controlling past and future seafloor emissions. Here, we report the distribution, petrographic (thin section, electron backscatter diffraction), isotopic (d13C, d18O) and lipid biomarker composition of methane-derived carbonates collected from Leirdjupet Fault Complex, SW Barents Sea, at 300 m depth during an ROV survey in 2021. Carbonates are located inside a 120 x 220 m elongated pockmark and form <10 m2 bodies protruding for about 2 m above the adjacent seafloor. Microstructural analyses of vein-filling cements showed the occurrence of 3 to 5 generations of isopachous aragonitic cement separated by dissolution surfaces indicative of intermittent oxidizing conditions. The integration of phase-specific isotopic analysis and U/Th dating showed d13C values between -28.6‰ to -10.1‰ and d18O between 4.6‰ and 5.3‰, enabling us to track carbonate mineral precipitation over the last ~8 ka. Lipid biomarkers and their compound-specific d13C analysis in the bulk carbonate revealed the presence of anaerobic methanotrophic archaea of the ANME-2 clade associated with sulfate-reducing bacteria of the Seep-SRB1 clade, as well as traces of petroleum. Our results indicate that methane and petroleum seepage in this area followed a similar evolution as in other southernmost Barents Sea sites controlled by the asynchronous deglaciation of the Barents Sea shelf, and that methane-derived carbonate precipitation is still an active process at many Arctic locations.